The Effect of Being Planned Pregnancy and Number of Pregnancies on Social Appearance Anxiety Level of Pregnant Women - Altıparmak, Sümeyye; Yılmaz, Ayşe Nur (My University, 2021)
Aim: In this study, it was aimed to examine the effect of being planned pregnancy and number of pregnancies on the social appearance anxiety level of pregnant women.Material and Method: Cross-sectional nature of the sample of the research conducted in a public hospital in eastern Turkey has created 426 pregnant women who were admitted for routine examination. The data were collected using “Personal Information Form” and “Social Appearance Anxiety Scale (SAAS)”. In statistical evaluation; In addition to descriptive statistics (number, percentage, mean, standard deviation, min-max), Cronbach’s alpha, pearson correlation, chi-square and independent groups t test were used.Results: In this study, it was determined that social appearance anxiety during pregnancy was not affected by the number of pregnancies, but women who had an unplanned pregnancy had a higher level of social appearance anxiety compared to women who had a planned pregnancy (p=0.008). In addition, it was found that primary school graduates had a significantly higher level of social appearance anxiety than high school and university graduates (p=0.009). It was observed that as the age and gestational week of the pregnant increased, their social appearance anxiety levels decreased significantly (p=0.002; p=0.039, respectively). It was determined that pregnant women whose income was less than their expenses had a higher level of social appearance anxiety compared to pregnant women with a traditional family structure compared to those with a nuclear family structure (p= 0.036; p=0.008, respectively).Conclusion: In this study, social appearance anxiety in pregnant women was not affected by the number of pregnancies. However, social appearance anxiety was experienced more in unplanned pregnancies and social appearance anxiety during pregnancy was affected by age, educational status, economic status, family structure and gestational week.
Keywords: Pregnant; Planned Pregnancy; Number of Pregnancies; Social Appearance Anxiety